مسببات الاسهال الطفيلية والفطرية والبكتيرية للمرضى المراجعين لمركز الزهراء الصحي في قضاء سوق الشيوخ , ذي قار , جنوب العراق - عبد علي محمد, زينب; نعيم عبد, انتظار; ستار عبود, ميثاق (University of Thi-Qar Journal of Science, 2011)
The current study included examination of 264 stool samples collected from patients attending Al Zahraa health center, Suq Al-Shuyukh district, during the period from January till December 2009, the samples were examined by direct smear method and concentration method to detect the intestinal parasites.After that, the samples were cultured and incubated to diagnose the pathogenic bacterial and fungal agents, no significant differences were shown in the infection of both sexes and age groups.The percentage of males infection (56.8 %) was higher than that in females (43.2 %).The higher percentage of infection (60.2 %) was found in age group ≤10 years, and the most common pathogens of diarrhea were the intestinal parasites (68.9 %) included infection with intestinal parasites only (26.5 %), intestinal parasites with pathogenic bacteria (22 %), intestinal parasites with fungal agents (40.9 %) and intestinal parasites with pathogenic bacteria and fungal agents (15.5 %).The highest percentage of parasitic infections was found in E. histolytica (42.8 %), the percentage of infection with pathogenic bacteria was (65.2 %) which included the infection with pathogenic bacteria only (4.9 %), pathogenic bacteria with fungal agents (22.8 %) and the highest percentage of pathogenic bacterial infection was in E. coli (8.3 %), the percentage of infection with fungal agents was 3.4 % and the highest percentage of fungal agents infection was that of C. albicans (14 %)